Integrating DNA and RNA sequencing for enhanced pathogen detection in respiratory infections - Dejian Gu; Jie Liu; Jiaping Wang; Yuting Yi; Yuxing Chu; Rui Gao; Hao Liu; Jun She; Binghuai Lu (Journal of Translational Medicine)
Abstract Background The clinical value of shotgun metagenomic next-generation sequencing (mNGS) in improving the detection rates of respiratory pathogens is well-established. However, mNGS is complex and expensive. This study designed and evaluated the performance of targeted NGS (tNGS) in diagnosing respiratory infections. Methods We retrospectively included samples from 281 patients with lower respiratory tract infections to establish thresholds of pathogens. Subsequently, target pathogens were selected and a probe hybridization system was established. The performance and clinical manifestations of tNGS for 306 pathogens were evaluated using clinical and simulated samples. Results The tNGS method took 16 h with sequencing data sizes of 5 M reads. The limit-of-detection of tNGS was 100–200 CFU/mL, respectively. Bioinformatics simulation confirmed the method’s high specificity and robustness. In 281 patients of clinical validation cohort, tNGS exhibited a sensitivity of 97.73% and specificity of 75.41% compared to the composite reference standard, which notably surpasses those of culture-based and conventional microbiological methods (CMT). In detecting bacterial and viral infection, tNGS demonstrated superior sensitivity relative to CMT. Notably, 61.40% of target viruses were subtype-resolved with the initial establishment of reliable typing cutoffs, with the subtyping results being completely consistent with the PCR results. tNGS allowed for concurrent identification of antimicrobial resistance (AMR) markers and viral subtyping. 80.56% of AMR markers identified by tNGS were consistent with antimicrobial susceptibility testing. Conclusion This research established the robust performance of our tailored tNGS assay in the simultaneous detection of DNA and RNA pathogens, underscoring its prospective suitability for widespread use in clinical diagnostics.